Pengaruh Keseimbangan Kehidupan Kerja Terhadap Kinerja Karyawan Melalui Mediasi Kepuasan Kerja Karyawan Unit Pelaksana Teknis dan Balai Sidoarjo Dinas Sosial Provinsi Jawa Timur - Faustina, Novia Gladys; Julianti, Emma (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The purpose of this study was to examine the effect of work-life balance on employee performance through the mediation of job satisfaction Unit Pelaksana Teknis dan Balai Sidoarjo Dinas Sosial Provinsi Jawa Timur. The object of this research was carried out in one of the Sidoarjo regional government offices. This research was conducted using quantitative methods. The population and sample used are all employees with a total of 81 respondents. Data collection uses a Likert Scale with quantitative data and how to distribute questionnaires offline by using paper sheets to be distributed to respondents/employees. Data analysis in this study fully uses the help of the Smart PLS version 3.0 software program. The results of this study indicate that work-life balance has a significant influence on employee performance. Work-life balance has a significant influence on job satisfaction. Job satisfaction has a positive but not significant effect on employee performance. Job satisfaction is not able to mediate the effect of work-life balance on employee performance.